Comparison between short and long‐term outcomes after minimally invasive versus open primary liver resections for hepatocellular carcinoma: A 1:1 matched analysis. Issue 4 (1st June 2021) - Goh, Brian K. P.; Syn, Nicholas; Koh, Ye‐Xin; Teo, Jin‐Yao; Cheow, Peng‐Chung; Jeyaraj, Prema R.; Chow, Pierce K. H.; Ooi, London L. P. J.; Chung, Alexander Y. F.; Chan, Chung‐Yip
Abstract: Background: This study aims to compare the short‐ and long‐term outcomes of patients undergoing minimally invasive liver resection (MILR) versus open liver resection (OLR) for nonrecurrent hepatocellular carcinoma (HCC). Methods: Review of 204 MILR and 755 OLR without previous LR performed between 2005 and 2018. 1:1 coarsened exact matching (CEM) and 1:1 propensity‐score matching (PSM) were performed. Results: Overall, 190 MILR were well‐matched with 190 OLR by PSM and 86 MILR with 86 OLR by CEM according to patient baseline characteristics. After PSM and CEM, MILR was associated with a significantly longer operation time [230 min (interquartile range [IQR], 145–330) vs. 160 min (IQR, 125–210), p < .001] [215 min (IQR, 135–295) vs. 153.5 min (120–180), p < .001], shorter postoperative stay [4 days (IQR, 3–6) vs. 6 days (IQR, 5–8), p = .001)] [4 days (IQR, 3–5) vs. 6 days (IQR, 5–7), p = .004] and lower postoperative morbidity [40 (21%) vs. 67 (35.5%), p = .003] [16 (18.6%) vs. 27 (31.4%), p = .036] compared to OLR. MILR was also associated with a significantly longer median time to recurrence (70 vs. 40.3 months, p = .014) compared to OLR after PSM but not CEM. There was no significant difference in terms of overall survival and recurrence‐free survival. Conclusion: MILR is associated with superior short‐term postoperative outcomes and with at least equivalent long‐term oncological outcomes compared to OLR for HCC.